Analysis Content of Organic Matter in Sediment and Abundance Macrozoobenthos in Kuala TanjungWaters Batubara District - Paul Rozeki Sinaga; Syahril Nedi; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in March 2016 in the waters of Kuala Tanjung,BatubaraDistrict, North Sumatra Province. General objective of this study wastodetermine the general condition of the aquatic environment Kuala Tanjung, andin particular is to know the type and abundance of macrozoobenthos, then therelationship of sedimentary organic matter content with abundance ofmacrozoobenthos. The method used in this research is survey method. Analysisresult done moderate polluted water conditions through the value through thevalue of diversity index (H ') ranged from 1.67 to 2.58. Dominance index value(C) ranges from 0.19 to 0.37. Value uniformity (e) ranges from 0.39 to 0.57.Macrozoobenthos were found as many as 9 species of gastropod class, and 3species of bivalves class. Abundance obtained ranged 32- 112 ind / m². Therelationship between the sedimentary organic matter content with abundance ofmacrozoobenthos obtained regression equation y = 46.18 + 1.576x with acoefficient of determination (R2) of 0.407 and a correlation coefficient (r) of0.638. This means that the relationship between the organic matter content ofsediment with an abundance of macrozoobenthos was moderately.Keywords: OrganicMaterials, macrozoobenthos, sediments and Kuala Tanjung